Upaya Perlindungan Hukum Terhadap Korban Kekerasan Psikologis dan Finansial - Asep Nursobah (Justice Amnesty Law and Undoing Journal, 2025)
The growth of the elderly population in Indonesia is greatly increasing. Maintain the survival of parents, and prevent the occurrence of danger, risks, and violations of human rights of parents is important. The issue discussed in this article is how the legal protection of the elderly who experienced psychological and financial violence. The research method used is socio-legal research. The results show that legal protection against the elderly has not been well implemented. Article 321 of the Civil Code provides for mutual obligations between parents and children. Article 9 of the Law on the Elimination of Domestic Violence regulates the scope of households and the prohibition of neglecting a person within the scope of the household. Article 8 of Law Number 13 Year 1998 on Elderly Welfare affirms that government, community and family are responsible for the improvement of elderly welfare. Implementation of Article 46 regarding the responsibility of the child to the elderly parent has not been effective. This can be seen of how many people who do not know the existence and content of the relevant provisions, many people neglecting their obligation ignoring their elderly parents. Legal protection of the elderly, which covers the recognition of the rights of the elderly, the protection of their interests and intentions, is not written in detail because the various provisions of how the Law are summarized. Sociologically, these provisions often escape the attention of the public, although the rules of non-law provide a special affirmation that supports the rule of law.